Double transverse foramina—an anatomical basis for possible vertebrobasilar insufficiency risk and vertebral artery injury - Tuncel Çini, Nilgün.; Nalla, Shahed; Mata Escolano, Federico.; Blanco Perez, Esther.; Valenzuela Fuenzalida, Juan José.; Orellana Donoso, Mathias Ignacio.; Sanchis Gimeno, Juan A. (MDPI, 2023)
Cervical vertebrae may exhibit the anomalous presence of a double transverse foramen (DTF) that may impact the anatomy of related structures that traverse the cervical region, such as the vertebral artery (VA). This retrospective anatomical study utilized CT angiography cervical scans to examine the prevalence of DTF, VA, and TF areas. The subjects were separated into two groups: normal TF (NTF group; 26 males and 21 females) and double TF (DTF group; 21 males and 24 females). The males presented significantly higher TF area values (30.31 ± 4.52 mm2) than the females (27.48 ± 1.69 mm2) in the NTF group (p = 0.006). The sex differences disappeared when a DTF was present (p = 0.662). There were no differences in the VA area values between the sexes in both the NTF and DTF groups (p = 0.184). No significant differences in the VA area values between males of the NTF and DTF groups (p = 0.485) were noted. The DTF subjects presented an increased VA/TF area ratio than the NTF subjects (p < 0.001). This study showed that DTF presence reduced the TF area. In contrast, the VA area did not change despite the decreasing TF area. This might be an anatomical risk for transient vertebrobasilar insufficiency in subjects with DTF, especially in females, because VA space in the TF is less in DTF subjects than in NTF subjects. This may lead to easy VA compression in DTF subjects following neck trauma.
Keywords: Anatomic variations; Computed tomography; Double transverse foramen; Vértebras cervicales; Columna vertebral; Arteria vertebral; Vertebrobasilar insufficiency